PENTINGNYA PENDIDIKAN KARAKTER DI SEKOLAH: MEMBANGUN GENERASI YANG BERETIKA DAN BERTANGGUNG JAWAB - Rahmani, Rahmani; Aura Putri Parhiyangan; Izzatunnajiah, Izzatunnajiah; Suptiani, Yulinda; Azmi, Nazrul (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Character Education, it is really necessary not only in school but also at home, and in social environments. This article discusses the importance of character education in schools as a foundation in building an ethical and responsible generation. In an era of globalization that is full of moral and social challenges, character education is the key to forming individuals who are not only academically intelligent, but also have integrity and concern for the surrounding environment. Through a holistic approach, character education is expected to develop positive values such as honesty, discipline and empathy. This article also examines the various methods of implementing character education in schools, as well as their impact on students' behavior in daily life. Through effective character education, it is hoped that students will be able to become individuals who have integrity, are able to make wise decisions, and contribute positively to society. In addition, character education also serves as a foundation for building an inclusive learning environment, respecting diversity, and creating harmonious social relationships in schools. The implementation of character education requires collaboration between teachers, parents, and the surrounding environment to ensure that these values can be applied consistently in the daily lives of students. Thus, character education is expected to be able to create a better and more civilized society, as well as create the next generation who are ready to face future challenges.